THE IMPACT OF AI DRIVEN PERSONALIZATION ON CUSTOMER ENGAGEMENT AND LOYALTY - Gunawan, Hendra; Suroso, Adi (Penelitian dan Pengembangan Ilmu, 2025)
The rapid growth of the global e-commerce industry, which is expected to reach USD 5.8 trillion by 2023, is driving companies to adopt artificial intelligence (AI)-based personalization to enhance customer experience. Leveraging big data, machine learning, and natural language processing (NLP), AI personalization enables real-time, tailored interactions that have been shown to increase conversions by up to 30% and customer loyalty by up to 84%. However, issues such as data privacy concerns, algorithmic bias, and digital fatigue due to over-personalization are major challenges. This study conducts a narrative review of the impact of AI-based personalization on customer engagement and loyalty in the e-commerce context. The study integrates multidisciplinary perspectives from marketing, information technology, and consumer psychology, and synthesizes selected literature (2015–2025) from Scopus, Web of Science, and Google Scholar databases. The findings suggest that AI personalization enhances customer engagement through recommendation systems, NLP-based chatbots, and predictive analytics, which ultimately drives loyalty. Trust and perceived content relevance act as key mediators in the relationship, while privacy concerns and information fatigue may decrease its effectiveness. This study contributes to the development of a theoretical framework on the AI–engagement–loyalty relationship and provides practical guidance for industry players to design more ethical, transparent, and sustainable personalization strategies.